The Relationship Between Eye And Hand Coordination On Volleyball Top Passing Skills In Extracurricular High School Negeri 2 Bengkulu Central - Tomi, Debi Andri; Perdima, Feby Elra; Anggara , Deffri (Universitas Dehasen Bengkulu, 2025)
This study aims to obtain an overview of the extent of the Relationship between Eye and Hand Coordination to Bolavoli Upper Passing Skills in Extracurricular at SMA Negeri 2 Bengkulu Tengah. In accordance with the problems and research objectives, this study used a correlation method, namely correlation analysis techniques with product moment statistics, this study used a sample of 17 athletes from SMA Negeri 2 Bengkulu Tengah who were taken with purposive sampling technique. The results of the data obtained from the relationship of hand eye coordination to the upper passing skill, namely the upper obtained thitung = 0.888> rtabel = 0.482 at the significance level α = 0.05. Thus, Ha which says there is a significant relationship between hand eye coordination and upper passing skills is accepted, consequently H0 is rejected. Thus it can be concluded that there is a significant relationship between hand eye coordination and the ability to pass over the extracurricular bolavoli students of SMA Negeri 2 Bengkulu Tengah with a value of rx.y = 0.888 > r (0.05) (15) = 0.482. dination, top passing